Tree and tree-like species of Mexico: Apocynaceae, Cactaceae, Ebenaceae, Fagaceae, and Sapotaceae - Ricker, Martin; Valencia-Avalos, Susana; Hernández, Héctor M.; Gómez-Hinostrosa, Carlos; Martínez-Salas, Esteban M.; Alvarado-Cárdenas, Leonardo O.; Wallnöfer, Bruno; Ramos, Clara H.; Mendoza, Pilar E. (Revista mexicana de biodiversidad, 2016)
Trees or tree-like plants are defined here broadly as perennial, self-supporting plants with a total height of at least 5m, without considering ascending leaves or inflorescences, and with 1 or several erect stems with a diameter of at least 10cm. In this third contribution of the taxonomic compilation of Mexico's native tree species, 271 species are presented: 27 in the family Apocynaceae (26% endemic), 63 in the Cactaceae (79%), 17 in the Ebenaceae (35%), 123 in the Fagaceae (60%), and 41 in the Sapotaceae (22%). Several cactus genera are endemic to Mexico, notably Neobuxbaumia with 10 species and heights up to 22m. The oak genus Quercus with 122 species is the most species-rich genus of Mexican trees. Several species are reported to reach heights of 60m (Aspidosperma desmanthum, Quercus benthamii, Q. corrugata, and Manilkara chicle). All species are listed in an appendix, including the original publication, references of taxonomic revisions, in some cases synonyms, existence of subspecies or varieties, maximum height in Mexico, and the indication if the species is endemic to Mexico. Las plantas arbóreas o arborescentes se definen en este trabajo en un sentido amplio como plantas perennes que se pueden sostener por sí solas, con una altura total de al menos 5 m, sin considerar hojas o inflorescencias ascendentes y con 1 o varios tallos erectos de un diámetro de al menos 10 cm. En esta tercera contribución de la recopilación de las especies arbóreas nativas de México, se presentan 271 especies: 27 de la familia Apocynaceae (26% endémicas), 63 de Cactaceae (79%), 17 de Ebenaceae (35%), 123 de Fagaceae (60%) y 41 de Sapotaceae (22%). Algunos géneros de Cactaceae son endémicos en México, notablemente Neobuxbaumia con 10 especies y alturas de hasta 22 m. Con 122 especies, Quercus es el género arbóreo más diverso en especies de México. Algunas especies se registran con alturas de hasta 60 m (Aspidosperma desmanthum, Quercus benthamii, Q. corrugata y Manilkara chicle). Todas las especies se enlistan en un apéndice que incluye el nombre científico, los datos de su publicación original, referencias de revisiones taxonómicas, en algunos casos sinónimos, la existencia de subespecies o variedades, la altura máxima en México y la indicación de si la especie es endémica de México.